1976
DOI: 10.1136/bjo.60.9.661
|View full text |Cite
|
Sign up to set email alerts
|

Uveal colobomata and Klinefelter syndrome.

Abstract: Most multiple congenital abnormality syndromes associated with uveal colobomata have their origins dating from before intrauterine development. Causative genetic and chromosomal influences were reviewed (James, Karseras, and Wybar, 1974), but associated abnornalities of the sex chromosomes were not observed in their series and are a rare occurrence in the literature. It is of interest therefore to record uveal colobomata occurring in a patient with Klinefelter syndrome and to discuss the possible implications.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1981
1981
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 7 publications
(2 reference statements)
0
3
0
Order By: Relevance
“…Ocular disorders in KS include uveal coloboma [ 5 ], choroidal atrophy [ 6 ], retinal degeneration [ 7 ], retinal vascular hypoplasia [ 8 ], cataracts [ 9 ], glaucoma [ 9 ], microphthalmia [ 10 ], and aniridia [ 11 ]. However, diabetic retinopathy has seldom been reported [ 4 ], and to the best of our knowledge, there have been no previous reports of severe PDR requiring vitrectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Ocular disorders in KS include uveal coloboma [ 5 ], choroidal atrophy [ 6 ], retinal degeneration [ 7 ], retinal vascular hypoplasia [ 8 ], cataracts [ 9 ], glaucoma [ 9 ], microphthalmia [ 10 ], and aniridia [ 11 ]. However, diabetic retinopathy has seldom been reported [ 4 ], and to the best of our knowledge, there have been no previous reports of severe PDR requiring vitrectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Ocular abnormalities are uncommon in Klinefelter syndrome (Duke-Elder 1976). Uveal colobomata (Francois et al 1970;Hashmi & Karseras 1976), bilateral anophthalmos (Wetter et al 1974), and unilateral corneal opacities (Boreaux et al 1969) have been reported. Mild lens opacities have been described in patients who have both Klinefelter syndrome and myotonic dystrophy (Sparkes et al 1973;Fiol et al 1975).…”
Section: Discussionmentioning
confidence: 99%
“…Ocular abnormalities, especially retinal disord e r s , a re uncommon in Klinefelter syndrome (4). Howeve r, ocular malformations associated with Klinefelter s y n d rome are described in the literature, including bilateral anophthalmos (5), aniridia (6), iris coloboma (7,8), Peters anomaly (9), choroidal coloboma (6), hereditary retinoblastoma (10) and incontinentia pigmenti (11). Chorioretinal findings associated with Klinefelter syndrome are diffuse choroidal atro p h y (12) and degeneration of the retinal pigment epithelium (13).…”
Section: Introductionmentioning
confidence: 99%